Analysis of incidence of lung cancer in various states of the USA. (10th December 2014) - Vyas, Riddhi; Haque, Syed; Mital, Dinesh P.; Srinivasan, Shankar
Lung cancer is the second most deadly cancer in this world after prostate cancer and breast cancer. Based on the past research, smoking is the primary cause of the death in lung cancer by age, race and gender. In this research, we have used National Inpatient Sample and census population for the state of CA, FL, TX, NY, IL, RI, VA, SC, and WI to determine the association of geographical variation with the risk factors by population. We have confirmed that incidence of lung cancer cases in CA (biggest state) are lower than smaller states like RI and VA. We confirmed our hypothesis that bigger state need not have to have higher incidence rate, but other like race, gender, pollution play an important role in increasing the occurrences.